Biochemical nutritional indicators in children with protein energy malnutrition attending Kanti Children Hospital, Kathmandu, Nepal - Mishra, SK; Bastola, SP; Jha, B (Kathmandu University Medical Journal, 2010)
Background: Nutrition is the science of food and its relationship to health. Nutritional status is one of the key indicators of health Nutritional status of Nepal is not satisfactory. Especially Protein Energy Malnutrition (PEM) in Nepal is a very common problem in children under five years of age. There are number biochemical parameters which become altered during protein energy malnutrition. Objectives: The objectives of the study are to determine biochemical nutritional indicators among children suffering from PEM and to compare all biochemical parameters with well nourished children and also to determine the factors affecting PEM among children under five years. Materials and methods: The study design was cross sectional, descriptive study with control. Children between ages 6 to 59 months attending outpatient department (OPD) and wards of Kanti Children's Hospital (KCH), Maharajgunj, Kathmandu, Nepal were purposively selected. The sample size was calculated by using prevalence of malnutrition in Nepalese context and allowable error of 10 %, a total of 120 cases which include 60 PEM cases and 60 controls were selected. They were grouped into two groups based on whether they are above or below the 80% of 50th percentile of weight for height based on growth chart of National Centre of Health Statistics 3 (NCHS), USA. Results: The educational status of parents of children with PEM was found to be significantly less (p